Deux mois à la Légion : une autre vision de la forêt - François-Michel Le Tourneau (Confins)
This text presents reflections on my participation in the "jungle platoon leader" training course organized by the French Foreign Legion in its training center in French Guiana, the Training Centre in Equatorial Forest (CEFE). Besides describing the running of the course in the manner of a field book, I compare the teachings received on this occasion with others from other contexts, including with my experience among Native Americans. In taking stock of the contributions of this adventure for the practice of geography in the Amazonian forest, I finally answer a question that Molière would not have disowned: "What the Hell would he be doing in this galley?".